Relationship of High Molecular Weight Adiponectin with Female Breast Cancer - Banori, Alia (International Journal of Pathology, 2020)
Background: Role of serum adiponectin level is very important in the prediction of cancer. Regarding breast cancer, adiponectin’s role is still under-investigation among women of pre and postmenopausal stage of life.Objective: To determine serum levels of HMW adiponectin in female patient of breast cancer.Methods: This is a case control study.This study consisted of 300 female subjects. Among which 150 consisted of patients having breast cancer and 150 consisted of normal healthy females as a control.This study was conducted in IRNUM Hospital Peshawar, Khyber Pakhtunkhwa (KPK). The duration of the study was 12 months i.e. from March 2016 to March 2017. Fasting blood samples were obtained from the participants and were analyzed for serum adiponectin level.Results: Significantly low adiponectin level was observed in cases than in controls with (P= 0.001). No significant difference was found in blood sugar level among both the groups (P=0.28). Significantly high level of serum insulin was found in patients having breast cancer as compared to control with (P= 0.02).Conclusion: The current study shows that serum adiponectin level is markedly decreased in breast cancer patients. It shows an inverse relationship with breast cancer, suggesting its protective role in breast cancer.